2019
DOI: 10.3138/jvme.0517-069r
|View full text |Cite
|
Sign up to set email alerts
|

Twitter in the Veterinary Diagnostic Imaging Classroom: Examination Outcomes and Student Views

Abstract: Radiographic lesion identification and differential diagnosis list generation can be difficult for veterinary students; thus, a novel means of distributing cases for study could improve students’ engagement and learning. The goal of this study was to determine whether using Twitter as an adjunct means of studying diagnostic imaging would improve student outcomes on the final exam for a radiology course. A secondary goal was to determine students’ preferred means of accessing additional cases for study. Twitter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Therefore, to reduce the number of inconclusive diagnoses resulting from failures in forwarding materials to the VDLs, it is necessary to implement measures to minimize these problems. The use of social media for teaching and improving the speed of diagnoses in Veterinary Medicine (Bernardo et al 2013, Tenhaven et al 2013, Mekaru & Brownstein 2014, Haustein et al 2015, Kedrowicz et al 2016, Englar 2017, Ober 2019, Saadeh et al 2021, Sellers et al 2021, Trittmacher et al 2021, Woodard et al 2021) and telemedicine (Farahani & Pantanowitz 2015, Bertram & Klopfleisch 2017 grows exponentially. The use of smartphones and media during visits to rural properties and in the guidance to veterinarians on the procedures necessary for sending samples to the VDLs, respectively, showed the potential to stimulate improvements in animal health (Karimuribo et al 2016, Miltenburg et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to reduce the number of inconclusive diagnoses resulting from failures in forwarding materials to the VDLs, it is necessary to implement measures to minimize these problems. The use of social media for teaching and improving the speed of diagnoses in Veterinary Medicine (Bernardo et al 2013, Tenhaven et al 2013, Mekaru & Brownstein 2014, Haustein et al 2015, Kedrowicz et al 2016, Englar 2017, Ober 2019, Saadeh et al 2021, Sellers et al 2021, Trittmacher et al 2021, Woodard et al 2021) and telemedicine (Farahani & Pantanowitz 2015, Bertram & Klopfleisch 2017 grows exponentially. The use of smartphones and media during visits to rural properties and in the guidance to veterinarians on the procedures necessary for sending samples to the VDLs, respectively, showed the potential to stimulate improvements in animal health (Karimuribo et al 2016, Miltenburg et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…A recent competency-guided review of an equine veterinary program at the Colorado State University identified that up to 32.4% of the students considered the radiology competencies were covered in "not enough detail". 5 Research in teaching of veterinary radiology is scarce and most studies focus on aspects of formal lecturing such as the impact of early implementation of radiology in the veterinary curriculum, 6,7 or the use of class enhancements, 8,9 recorded pre-classroom assignments, 10,11 or self-directed learning methods, 7,12 with variable results on improving exam scores. Overall, there appears to be a trend toward better outcomes with the implementation of interventions that increase student participation or provide additional support material.…”
Section: Introductionmentioning
confidence: 99%
“…Facebook, Twitter, and Instagram have been the most social media used in VM(TENHAVEN et al, 2013;WHITING;KINNISON;MOSSOP, 2016;OBER, 2019;SCALLA VULCANI et al, 2020;DO NASCIMENTO SENA et al, 2021).Most of the modern virtual learning environments allow the simulation of different events and real processes, giving a more realistic and coherent learning experience(ESPITIA et al, 2019;EVANS et al, 2019). Although DE methods cannot completely replace the classes and practical training in VM, it offers several advantages.…”
mentioning
confidence: 99%